UAV-Based Gigapixel Panoramic Image Acquisition Planning with Ray Casting-Based Overlap Constraints. (2nd May 2019) - Zhang, Shuhang; Liu, Chun; Zhou, Yuan
Abstract : Panoramic imaging is information-rich, low-cost, and effective. In panoramic image acquisition, unmanned aerial vehicles (UAVs) have a natural advantage that owes to their flexibility and relatively large observation ranges. Using a panoramic gimbal and a single camera may be the most common means of capturing gigapixel panoramas. In order to manage the constraints of UAV power and facilitate the use of a variety of camera lenses, an effective and flexible method for planning UAV gigapixel panorama acquisitions is required. To address this need, a panoramic image acquisition planning method is proposed in this paper. The method defines image overlaps via a ray casting procedure and then generates an acquisition plan according to the constraints of horizontal and vertical overlap thresholds. This method ensures the completeness of the panorama by maintaining the overlap between adjacent images. Two experiments, including simulated and field cases, were performed to evaluate the proposed method through comparisons with an existing panorama acquisition plan. Results showed that the proposed method can capture complete panoramas with fewer images.